Pathophysiology of severe malaria in children. - Maitland, K; Marsh, K (2004)
Over the past decade there has been a growing recognition that the rationalization of severe malaria in children into the two major syndromes of cerebral malaria and severe malaria anaemia is much too simplistic. Indeed, it has become apparent that death from severe malaria may arise from a wider spectrum of pathophysiological disorders with many features in common with the derangements seen in sepsis syndromes. Amongst these derangements acidosis has emerged as a central feature of severe malaria and the major predictor of a fatal outcome. We review the improved understanding of the pathophysiology of severe malaria through a series of clinical scenarios that reflect more accurately the clinical diversity of severe malaria in African children. Current therapeutic challenges are discussed and research priorities are highlighted.